2018
DOI: 10.1016/j.jvs.2017.05.120
|View full text |Cite
|
Sign up to set email alerts
|

Brachial vein transposition is a promising ultimate upper limb autologous arteriovenous angioaccess despite its many pitfalls

Abstract: Despite many pitfalls for the surgeon, BrVT offers promising long-term patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Surgical PRA to radial vein outflow AVF for staged brachial vein for staged brachial vein transposition is a successful surgical strategy. 22,23 A pAVF creation for brachial vein outflow and subsequent staged elevation represents a promising opportunity for an autogenous access which should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical PRA to radial vein outflow AVF for staged brachial vein for staged brachial vein transposition is a successful surgical strategy. 22,23 A pAVF creation for brachial vein outflow and subsequent staged elevation represents a promising opportunity for an autogenous access which should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported similar results, with reduced use of grafts. 9,11,12,17,19 Other authors have compared the results of brachial vein transposition with those of arteriovenous grafts for hemodialysis. In 2017, Pham et al 1 compared 29 patients who underwent superficial displacement of the brachial vein and 36 patients who underwent construction of prosthetic arteriovenous access.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, reported brachial vein transposition patency was substantially lower than rates reported by other authors. 1,9,[11][12][13] The single intervention surgical technique was chosen, as described by Bazan and Schanzer. 8 Two-stage surgery for superficial transposition of the brachial vein has been described by several authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In patients where a long-term vascular access for hemodialysis rather than a catheter is indicated but have inadequate superficial and basilic veins, a choice can be made between a graft or an elevated brachial vein fistula. [5][6][7] A pAVF creation of a radial artery-radial vein anastomosis with the Ellipsys ® device combined with a secondary brachial vein elevation (BrVE) offers an attractive alternative, combining a minimally invasive first stage, a moderate flow radial artery pAVF, and added mid-arm mature brachial vein length for elevation and cannulation. In this report, we review our technique and experience in this subset of patients.…”
Section: Introductionmentioning
confidence: 99%